Identification of PPREs and PPRE associated genes in the human genome: insights into related kinases and disease implications - Saha, Pritha; Talwar, Priti (Frontiers in Immunology, 2024)
Peroxisome Proliferator-Activated Receptors" (PPARs) belong to the class of transcription factors (TF) identified as Nuclear Receptors (NR). Upon activation by peroxisome proliferators (PPs), PPARs modulate a diverse range of genes, consequently regulating intra-cellular lipid metabolism, glucose uptake, apoptosis, and cell proliferation. Subsequent to the heterodimerization of Retinoid X Receptors (RXR) with PPARs induced by the binding of activators to PPARs, facilitates the binding of the resulting complex to Peroxisome Proliferator-Activated Receptors Response Elements (PPRE), with a consensus sequence 5'AGGTCANAGGTCA-3', and regulate the transcription of the targeted genes. This study aimed to explore PPRE within the human genome, focusing on genes involved in the PPAR pathway and related pathophysiological conditions. The NCBI Genome Workbench and UCSC Genome Browser were employed for PPRE screening and elucidation of associated genes, identifying 660 genes, including 29 kinases. The engagement of these kinases in various biological pathways, such as apoptosis, platelet activation, and cytokine pathways, revealed from the functional enrichment analysis using FunRich, ToppGene, and ShinyGO, illuminates the multifaceted role of PPAR in the regulation of cellular homeostasis and biological processes.Network analysis using NDEx reveals the kinases interact with approximately 5.56% of the Human Integrated Protein-Protein Interaction rEference (HIPPIE) network. Disease association analysis using DisGeNET and COSMIC datasets revealed the significant roles of these kinases in cellular processes and disease modulation, underscoring the significance of these findings in human pathophysiology, with the potential to guide future research and therapeutic strategies targeting these kinases for disease management and intervention.